The Laryngectomee Substitute Voice: Image Processing of Endoscopic Recordings by Fusion with Acoustic Signals - Lohscheller, J.; Döllinger, M.; Schuster, M.; Eysholdt, U.; Hoppe, U. (Methods of Information in Medicine, 2003)
Objectives: The most radical cancer therapy of the throat is the total excision of the larynx which postoperatively results in the loss of voice. A widely-used method of voice rehabilitation is the insertion of a silicone valve, which establishes an unidirectional connection between trachea and esophagus. Thus, during exhalation, air can be directed from the trachea into the esophagus. This air stream excites tissue vibrations of the esophagus and the hypo-pharynx which act as a substitute voice generator. Purpose of the current study is to present a technique for visualizing the dynamics of the substitute voice generating element.Methods: Digital high speed videos of the vibrating tissue are simultaneously recorded with the emitted acoustic signal. The high speed sequences are directly evaluated by a three-step knowledge based algorithm. It considers correlation between image and acoustic data, information about the gray value of each pixel, and continuity of tissue vibration. The temporal properties of an image series are investigated by evaluating the time dependent gray value at each pixel position.Results: The applicability of the algorithm is exemplar-ily demonstrated using the data of one male patient. It enables the identification of the regions within an image series which are mainly responsible for the acoustic signal. Additionally, the dynamics of tissue vibrations are visualized. The main propagation direction can be clearly identified.Conclusions: The new methodology summarizes the information about endoscopic and acoustic recordings of substitute voice into a single image. The results allow a first estimation of tissue velocity and elastic properties of oscillating tissue.
Keywords: Substitute voice; image processing; digital high speed camera; PE-segment